The genus Peramphithoe Conlan & Bousfield, 1982 from Korean waters (Crustacea: Amphipoda: Ampithoidae) - Kim, Young-Hyo; Hong, Soon-Sang; Conlan, Kathleen E.; Lee, Kyung-Sook (Zootaxa, 2012)
Four species of the genus Peramphithoe have been recorded in Korean waters. Herein we add two peramphithoid species,Peramphithoe chujaensis sp. nov. and P. eoa (Brüggen). The new species is easily distinguished from congeners by: (1)male antenna 2 with plumose setae ventrally, (2) male gnathopod 2, propodus 0.7 x as wide as long and palm excavated,(3) male pereopods 5–7, meri and carpi expanded, (4) in both sexes, gnathopod 1, carpus subequal in length to propodus.The newly recorded species in Korea, P. eoa is well accorded with the original description. A key to and description ofKorean peramphithoid species is also provided. To examine relationships among species in the genus Peramphithoe fromKorea, a morphological and molecular phylogenetic study was conducted using 657 bp of the gene for the mitochondrialcytochrome c oxidase subunit 1 (mtCO1). This gene showed good resolution as a molecular marker for species identification of the genus Peramphithoe in Korea.